Factors influencing home advantage in American collegiate football. Issue 2 (3rd April 2019) - Fullagar, Hugh H. K.; Delaney, Jace; Duffield, Rob; Murray, Andrew
ABSTRACT: This study investigated the effect of home advantage (HA) in NCAA Division I football, and assessed factors related to why HA may exist. Game location (home/away), points differential between team scores, distances between team stadiums (short [<483 km], moderate [484–836 km], long [837–1331 km] or very long [>1332 km]), crowd number, differences in team penalty counts (penalty differential), penalty yardage differential and time zone change (Eastward or Westward direction of travel) data from two non-consecutive NCAA college football seasons (2013 and 2016; 719 games; 222 teams) were obtained. Matches played at home were associated with a ~5 point advantage (ES = 0.58 ± 0.18). Away teams traveling >484 km resulted in a moderate disadvantage (~5 to 7 points, ES = −0.61 to −0.77). When crossing time zones in a Westerly direction resulted in a ~7.5 point disadvantage (ES = −0.82 ± 0.31) for away teams. When playing at Home, larger crowds resulted in a ~6 point advantage (ES = 0.67 ± 0.36), whilst larger crowds were negatively associated with performance (~8 points; 2 points) for away teams (ES = −0.97 ± 0.27). These results suggest HA exists in NCAA Division I football, particularly evident with larger crowds. These results provide evidence that could aid logistical or periodisation strategies in preparation for games.